(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Active magnetic bearing is the electromechanical device allowing to suspend the rotor of the electric machine. Friction is eliminated and high speed of rotation can be achieved. However, the parameters of the electromechanical system may change during operation. Adaptive control system allows to maintain stability under varying parameters.